Minucella, a new leafhopper genus from China (Hemiptera: Cicadellidae: Stegelytrinae) - Wei, Cong; Zhang, Yalin; Webb, M. D. (Zootaxa, 2008)
Minucella gen. n. and two species (M. divaricata sp. n. and M. leucomaculata (Li & Zhang) comb. n.) from southern China are described in the leafhopper subfamily Stegelytrinae. Difficulties in the delimitation of one of the included species, M. leucomaculata and its junior synonym Placidus maculates Li & Zhang, syn. nov., are discussed, and the observed variation is considered to be intraspecific. ‘Mud-puddling’ is recorded for the new genus and discussed for the subfamily.